Spillover Events of Infection of Brown Hares (Lepus europaeus) with Rabbit Haemorrhagic Disease Type 2 Virus (RHDV2) Caused Sporadic Cases of an European Brown Hare Syndrome‐Like Disease in Italy and Spain. Issue 6 (11th September 2016) - Velarde, R.; Cavadini, P.; Neimanis, A.; Cabezón, O.; Chiari, M.; Gaffuri, A.; Lavín, S.; Grilli, G.; Gavier‐Widén, D.; Lavazza, A.; Capucci, L.
Summary: Rabbit haemorrhagic disease virus (RHDV) is a lagovirus that can cause fatal hepatitis (rabbit haemorrhagic disease, RHD) with mortality of 80–90% in farmed and wild rabbits. Since 1986, RHDV has caused outbreaks in rabbits ( Oryctolagus cuniculus ) in Europe, but never in European brown hares ( Lepus europaeus, EBH). In 2010, a new RHDV‐related virus, called RHDV2, emerged in Europe, causing extended epidemics because it largely overcame the immunity to RHDV present in most rabbit populations. RHDV2 also was identified in Cape hare ( Lepus capensis subsp. mediterraneus ) and in Italian hare ( Lepus corsicanus ). Here, we describe two distinct incidents of RHDV2 infection in EBH that occurred in Italy (2012) and Spain (2014). The two RHDV2 strains caused macroscopic and microscopic lesions similar to European brown hare syndrome (EBHS) in hares, and they were genetically related to other RHDV2 strains in Europe. EBHs are common in Europe, often sharing habitat with rabbits. They likely have been exposed to high levels of RHDV2 during outbreaks in rabbits in recent years, yet only two incidents of RHDV2 in EBHs have been found in Italy and Spain, suggesting that EBHs are not a primary host. Instead, they may act as spillover hosts in situations when infection pressure is high and barriers between rabbits and hares are limited, resulting in occasional infections causing EBHS‐like lesions. The serological survey of stocked hare sera taken from Italian and Spanish hare populations provided an understanding of naturally occurring RHDV2 infection in the field confirming its sporadic occurrence in EBH. Our findings increase the knowledge on distribution, host range and epidemiology of RHDV2.